Constructing Electron Levers in Perovskite Nanocrystals to Regulate the Local Electron Density for Intensive Chemodynamic Therapy. Issue 16 (9th March 2021) - Zhao, Peiran; Jiang, Yaqin; Tang, Zhongmin; Li, Yanli; Sun, Bingxia; Wu, Yelin; Wu, Jiyue; Liu, Yanyan; Bu, Wenbo
Abstract: The local electron density of an atom is one key factor that determines its chemical properties. Regulating electron density can promote the atom's reactivity and so reduce the reaction activation energy, which is highly desired in many chemical applications. Herein, we report an intra‐crystalline electron lever strategy, which can regulate the electron density of reaction centre atoms via manipulating ambient lattice states, for Fenton activity improvement. Typically, with the assistance of ultrasound, the Mn 4+ −O−Fe 3+ bond in BiFe0.97 Mn0.03 O3 perovskite nanocrystals can drive valence electrons and free electrons to accumulate on Fe atoms by a polarization electric field originated from the designed lattice strain. The increase of electron density significantly improves the catalytic activity of Fe, decreasing the activation energy of BiFe0.97 Mn0.03 O3 ‐mediated Fenton reaction by 52.55 %, and increasing the . OH yield by 9.21‐fold. This study provides a new way to understand the sono‐Fenton chemistry, and the increased . OH production enables a highly effective chemodynamic therapy. Abstract : An intra‐crystalline electron lever strategy is proposed by constructing Mn‐doped BiFeO3 nanocrystals with a Mn 4+ −O−Fe 3+ bond lever, which can specifically increase the local electron density of the Fe reaction centre to improve the kinetics of chemodynamic therapy. This method is promising in future research on the quantitative regulation of electron density and on‐demand chemical reactivity adjustment.